1996
DOI: 10.1007/bf00041390
|View full text |Cite
|
Sign up to set email alerts
|

The petunia homologue of tomato gast1: transcript accumulation coincides with gibberellin-induced corolla cell elongation

Abstract: Gibberellins (GAs) regulate petunia corolla pigmentation and elongation. To study this hormone's effect at the molecular level, we used the tomato gast1 gene as a probe to isolate a gibberellin-induced gene (gip) from petunia corollas. The deduced sequence of gip exhibited 82% identity with GAST1 protein and contained a short, highly hydrophobic N-terminal region. High levels of gip expression were detected in elongating corollas and young stem intemodes. When detached corollas were grown in vitro in sucrose m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 27 publications
5
85
0
5
Order By: Relevance
“…Sequences are (a) RC153 from Ricinus communis (EMBL accession no. T24153); (b) N37340 from Arabidopsis thaliana (Newman et al 1994); (c) Os0951 from rice (Sasaki et al 1994); (d) PHGIPl from petunia (Ben-Nissan and Weiss 1996); (e) GASTl from tomato (Shi et al 1992); (f,g,i,j) GASA2,3,4,1 from A. thaliana (Herzog et al 1995); (h) RSIl from tomato (Taylor and Scheuring 1994); and (KIS) kistrin from the Malayan pit viper (Adler et al 1991). Identical residues are shaded and the numbers of identical residues (id/63) are indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequences are (a) RC153 from Ricinus communis (EMBL accession no. T24153); (b) N37340 from Arabidopsis thaliana (Newman et al 1994); (c) Os0951 from rice (Sasaki et al 1994); (d) PHGIPl from petunia (Ben-Nissan and Weiss 1996); (e) GASTl from tomato (Shi et al 1992); (f,g,i,j) GASA2,3,4,1 from A. thaliana (Herzog et al 1995); (h) RSIl from tomato (Taylor and Scheuring 1994); and (KIS) kistrin from the Malayan pit viper (Adler et al 1991). Identical residues are shaded and the numbers of identical residues (id/63) are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves were sprayed with solutions of hormones that have been implicated in plant-pathogen interactions, such as methyl jasmonate (50 uM), ethylene (ethephon 0.03 g/liter), and abscisic acid (100 uM), inducers of systemic acquired resistance, such as salicylic acid (5 mM) and isonicotinic acid (0.6 mM), and hormones that have been shown to affect steady-state levéis of mRNAs encoding some SN1 homologues in other plant species (Shi et al 1992;Herzog et al 1995;Ben-Nissan and Weiss 1996), such as indolacetic acid (20 uM) and GA (100 uM). In none of these treatments was induction of the SN1 mRNA observed.…”
Section: Lack Of Response Of Gene Stsnl To Abiotic and Biotic Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the GASA proteins are located in the cell wall, suggesting their function may relate to the cell wall extension or cell division. Existing research results show that GASA protein involved in promoting 9,18,23,45 or inhibiting 27,46 cell elongation and cell division 11,19,24,32 and other developmental processes, such as flowering time regulation.…”
Section: Gasas Involve In Plant Growth and Development Processmentioning
confidence: 99%
“…A variety of results from different plant species suggest that GAST-like genes are mainly involved in cell elongation and cell division. Expression data and mutant analyses in petunia (Petunia hybrida), for example, have suggested that the Gibberellic Acid Induced Petunia1 (GIP1) gene is involved in the elongation of the stem and the corolla (Ben-Nissan and Weiss, 1996;Ben-Nissan et al, 2004). Similarly, expression of tomato GAST1 has been associated with stem elongation (Shi et al, 1992), although plants either over-or underexpressing GAST1 did not display an altered phenotype (Shi and Olszewski, 1998).…”
mentioning
confidence: 99%